Technological Transformations in the Audiovisual Media Industry: A Case Study of Netflix - Nadir LAMARI & Ahmed Mahdi ZOUAOUI (Akofena)
Abstract: The audiovisual media industry has experienced profound transformations driven by technological innovation, fundamentally reshaping production, distribution, and consumption practices. This article examines Netflix as a case study to explore the critical technological shifts that have propelled the industry forward. As a pioneer in digital streaming, Netflix revolutionized traditional media through innovations in artificial intelligence, big data analytics, and interactive media technologies. The study delves into Netflix’s evolution from a DVD rental service to a global streaming giant, focusing on its subscription-based model, reliance on recommendation algorithms, and data-driven content strategies. Additionally, it assesses the technical challenges and competitive dynamics Netflix faces in an increasingly crowded market. The article also considers the social and cultural ramifications of these technological shifts, exploring how Netflix influences viewer preferences and public culture while navigating ethical considerations inherent in algorithmic recommendations. Through this analysis, the article offers insights into the future trajectory of audiovisual media and the implications of continued technological advancements. Keywords: Audiovisual Media; Netflix; Digital Streaming; Artificial Intelligence; Media Transformation